Exploring Growth Mindset to Enhance the Skills of Designing Learning Planning Tools among Islamic Elementary School Teacher Education Students - Nulinnaja, Ratna; El Wardah, Aunia Shifni; Fadhilah, Reni; Amalia, Sovi; Putra, Kivah Aha (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This research aims to explore how third semester students who are part of the Zoomers generation apply a growth mindset in preparing learning planning tools. With the unique characteristics possessed by Generation Z, such as openness to educational materials and tools, creativity, and adaptability, this research identifies the positive impact of a growth mindset on their skills in compiling and developing learning planning tools. The method used is a qualitative approach with observation, in-depth interviews and documentation. Data analysis uses 4 stages developed by Mileshuberman. The research results show that students believe that intelligence can be developed through effort, see challenges as opportunities to grow, and consider failure to be an important part of the learning process. They also demonstrate an open attitude to feedback and use the success of others as a source of inspiration. These findings confirm that the application of a growth mindset can improve the quality of learning planning tools prepared by students, as well as prepare them to face challenges in the world of education. This research provides important implications for the development of teacher education curricula, with an emphasis on developing a growth mindset as a key component in the learning process.